A STUDY OF THE TEACHING METHODS USED BY THE MATHEMATICS TEACHER IN MASOHI CITY'S JUNIOR HIGH SCHOOL - S R Litiloly; E Sohilait; M K Sidik (Faculty of Teacher Training and Educational Sciences, Pattimura University Indonesia, 2023)
Students are less able to comprehend and resolve mathematical issues as a result of reading mathematical content. Additionally, deductive mathematics learning necessitates the use of skills in mathematics instruction by the teacher to ensure that students comprehend and correctly answer mathematical issues. The teaching methods of teachers when students are learning are thus the subject of some research. The purpose of this study is to evaluate the mathematics instructors' delivery methods in Masohi City's junior high schools. The participants in this study were junior high school mathematics teachers in Masohi City, and they were chosen based on their educational background, length of employment, attendance at workshops, and/or other relevant strategies or the use of instructional materials. The mathematics teacher's teaching methodology is the subject of the study. A quantitative descriptive research methodology was adopted, in which the amount of data collected was stated in detail. Observation, questionnaires, and interviews with research participants are other methods used in data collection. When the research was being done, observations were made to watch what was happening. The purpose of the questionnaire is to determine how effectively the chosen teaching method can encourage students to use mathematics in their classwork, homework, and other performances. The interview was done to ascertain the accuracy of the questionnaire responses and to serve as a discussion starter for the results that would be discussed later.